2020
DOI: 10.9734/jammr/2020/v32i330385
|View full text |Cite
|
Sign up to set email alerts
|

Normative Orthodontic Treatment Need of Nigerian Adolescents – A Comparative Study of Three Major Ethnic Groups

Abstract: Objective: This study was carried out to assess and compare the normative orthodontic treatment need of adolescents aged 12 to 16 years from the three major ethnic groups in Nigeria. Methods: The study population comprised one thousand, four hundred and forty-nine (1449) adolescents selected from nine public schools within nine Local Government Areas from three (3) selected states (Lagos, Kano, Imo) in Nigeria. Randomization based on multistage sampling technique was used to determine the selected partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…On the other hand, a study conducted on 250 school children aged 11-14 years, and 250 patients aged 11-14 years in Turkey showed that 38.8% of the school population and 83.2% of the referred population needed definite orthodontic treatment need [17]. Other studies have also reported a higher finding than the present study [15,16,18,27]. The reported differences in normative orthodontic treatment need may be due to the different methods used and differences among the age groups studied.…”
Section: Discussioncontrasting
confidence: 70%
“…On the other hand, a study conducted on 250 school children aged 11-14 years, and 250 patients aged 11-14 years in Turkey showed that 38.8% of the school population and 83.2% of the referred population needed definite orthodontic treatment need [17]. Other studies have also reported a higher finding than the present study [15,16,18,27]. The reported differences in normative orthodontic treatment need may be due to the different methods used and differences among the age groups studied.…”
Section: Discussioncontrasting
confidence: 70%
“…[ 27 ] Differences may be due to age of study populations as malocclusion has been shown to worsen with age,[ 28 ] as well as ethnic variations in perceptions of beauty. Male participants were found to have a greater need for treatment than females as has been seen in studies in Greece[ 29 ] and Nigeria,[ 14 ] whereas a Syrian study did not find any sex predilection. [ 30 ]…”
Section: Discussionmentioning
confidence: 89%
“…This is slightly lower than the need of 38.1% assessed in adolescents in South Nigeria[ 18 ] but higher than 31.5% found in a similar population in North-Western Nigeria in which the Index of Complexity, Outcome, and Need was used. [ 14 ] The magnitude of need is however much lower than that found among Saudi Arabian children (55.4%). [ 19 ] This difference may be due to ethnic and racial variations as has been identified in another Nigerian study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By leveraging cutting-edge techniques and technologies, accelerated orthodontics (AO) helps to optimize the alignment of teeth while minimizing the treatment duration and, therefore, provides patients with quicker, more efficient, and aesthetically pleasing outcomes [8]. In fact, accelerated orthodontic techniques aim to address these disadvantages by reducing treatment duration, offering patients a faster and potentially more comfortable path to achieving their desired results with fewer associated challenges [2,9,10,11,12]. Indeed, accelerated orthodontics has revolutionized traditional dental practices by employing innovative techniques to expedite tooth movement and enhance treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%